Cellular enlargement - A new hallmark of aging? - Davies, Daniel M.; van den Handel, Kim; Bharadwaj, Soham; Lengefeld, Jette (Frontiers in Cell and Developmental Biology, 2022)
Years of important research has revealed that cells heavily invest in regulating their size. Nevertheless, it has remained unclear why accurate size control is so important. Recent studies using yeast and hematopoietic stem cells (HSCs) in vivo indicate that cellular enlargement is causally associated with aging. Here, we performed a broad literature analysis to evaluate the potential of cellular enlargement as a new hallmark of aging and to examine how cell enlargement is connected to other aging hallmarks. Furthermore, we highlight interesting work presenting a correlation between cell size and aging-related diseases. Taken together, we found mounting evidence motivating the further evaluation of cellular enlargement as a new hallmark of aging. Therefore, we encourage researchers from seemingly unrelated areas to take a fresh look at their data from the perspective of cell size.